2017
DOI: 10.1016/j.yjmcc.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale, tailor-made heart simulation can predict the effect of cardiac resynchronization therapy

Abstract: By integrating the complex pathophysiology of the heart, patient-specific, multi-scale heart simulation could successfully reproduce the response to CRT. With further verification, this technique could be a useful tool in clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…Researchers participating in the simulations were blinded to the outcome until the simulations were completed. The details of the simulation method were described previously [19,20] and are shown in the supplementary methods provided in Online Resource 1.…”
Section: Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers participating in the simulations were blinded to the outcome until the simulations were completed. The details of the simulation method were described previously [19,20] and are shown in the supplementary methods provided in Online Resource 1.…”
Section: Simulationmentioning
confidence: 99%
“…To save computational time and cost, we modeled only ventricles, and the time-varying elastance models of atria were connected with an electrical circuit analog of circulation ( Fig. 1a), the parameter values of which were adjusted for each patient [19,20,24] (see supplementary Table 2 in Online Resource 1). Finally, contractility of the ventricles was adjusted to match the EF and non-invasive arterial blood pressure of each patient.…”
Section: Patient-specific Heart Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing interest in dynamic models of electrical and muscle activity of the heart, which require adequate geometric modeling of the heart [23]. A study was conducted in [8], the purpose of which was to test the ability of simulation models of a particular patient to reproduce the response to cardiac resynchronization therapy (CPT) using the latest heart simulation technology. As a result, it was found that multiscale heart modeling for a particular patient can successfully reproduce the response to CRT.…”
Section: Fig 2 (A) a Drawing Made By Torrent-guasp Illustratingmentioning
confidence: 99%
“…Patient-specific models not only enhance physiological understanding of the diseasespecific processes involved in dyssynchronous HF and its treatment by CRT, but also can assist in personalized diagnostic, prognostic and treatment related support. To date, some feasibility studies containing small number of patients have shown that computer models have the potential to predict acute hemodynamic response to CRT 87,88 . In Chapter 2 we showed that personalized prediction of acute hemodynamic response did not improve by adding more detailed information on the electrical substrate in addition to interventricular dyssynchrony during intrinsic rhythm.…”
Section: Response To Crt: the Role Of Computer Modelingmentioning
confidence: 99%